Socioeconomic circumstances and lung function growth from early adolescence to early adulthood - Rocha, V (2021)
Background A reduced lung function in early adulthood is associated with respiratory and non-respiratory diseases and is a long-term predictor of mortality. This study investigated the association between early socioeconomic circumstances (SEC) and lung function growth trajectories from early adolescence until early adulthood. Methods We analysed data from the EPITeen population-based study, including adolescents born in 1990. Study waves occurred at 13, 17 and 21 years of age. Information on sociodemographic, behavioural and health factors, anthropometry and spirometry was collected. Early-life SEC were assessed using maternal education and paternal occupational position. The forced expiratory volume in the first second (FEV1) growth trajectories were drawn considering sex-and-height interactions over an 8-year period. Our sample included 2022 participants with complete information for the relevant variables. Results Participants from most disadvantaged SEC presented lower FEV1 at early adolescence compared to high-SEC counterparts, but differences seem to diminish with height growth. The effect of paternal occupational position in lung function growth trajectories was moderated by height, thus individuals from fathers with less advantaged occupational position had lower FEV1 at early adolescence, but they had a faster FEV1 growth over time. Conclusions Individuals from most disadvantaged SEC presented lower lung function at early adolescence compared to high-SEC counterparts; nevertheless, a catch-up growth was observed.